sTfR Sebagai Faktor Risiko Bangkitan Kejang Demam - Abdul Khanis; Tjipta Bahtera; Noor Wijayahadi (MEDIA MEDIKA INDONESIANA, 2010)
sTfR parameter as a risk factor of febrile seizuresBackground: Febrile seizures is the most often neurologic disorder in children and 2%-5% children under 5 years old have experienced febrile seizures. Prognosis of febrile seizures is good, however the seizure brings serious worries to the parents. Iron deficiency as a risk factor of febrile seizures is still controversial.Objective: To analyze iron deficiency with serum transferrin receptor (sTfR) parameter as a risk factor of febrile seizures in children.Method: Study design was case control with subjects 72 children aged 3 months – 5 years in Dr. Kariadi hospital on August 2009 – January 2010, 36 children with febrile seizures as case group and 36 children with febrile with no seizure as control group. Clinical data and blood sampling were recorded from study subjects for sTfR level measurement. Risk factors were analyzed with odds ratio (95% confidence interval) and multivariate logistic regression.Results: Mean sTfR level was 6.2 μg/mL (2.6-6.8) in case group and 2.0 μg/mL (1.8-2.3) in control group. Multivariate analysis showed iron deficiency with sTfR parameter was significantly as a risk factor for febrile seizures (p<0.001; OR=25.1; 95%CI 5.1-122.6). sTfR level could be used as febrile seizures indicator with sTfR level cut-off point was 2.55 μg/ml. Conclusion: sTfR parameter can be used is a risk factor for febrile seizures. ABSTRAKLatar belakang: Kejang demam merupakan kelainan saraf tersering pada anak dan 2%-5% anak di bawah umur 5 tahun pernah mengalami kejang demam. Prognosis kejang demam baik, namun cukup mengkhawatirkan bagi orang tuanya. Defisiensi besi sebagai faktor risiko bangkitan kejang demam masih kontroversial. Tujuan penelitian ini menganalisis defisiensi besi dengan parameter serum transferrin receptor (sTfR) sebagai faktor risiko bangkitan kejang demam pada anak.Metode: Penelitian kasus kontrol ini dengan subyek penelitian 72 anak berumur 3 bulan sampai 5 tahun di RSUP Dr. Kariadi pada Agustus 2009 – Januari 2010, 36 anak kelompok kasus dengan bangkitan kejang demam dan 36 anak kelompok kontrol dengan demam tanpa kejang. Subyek penelitian dicatat data klinis dan pengambilan darah untuk diperiksa kadar sTfR. Faktor risiko dianalisis dengan rasio odds (95% interval kepercayaan) dan multivariat regresi logistik.Hasil: Rerata kadar sTfR pada kelompok kasus 6,2 μg/mL (2,6-6,8) dan kelompok kontrol 2,0 μg/mL (1,8-2,3). Analisis multivariat menunjukkan defisiensi besi dengan parameter sTfR secara bermakna merupakan faktor risiko bangkitan kejang demam (p<0,001; OR=25,1; 95%CI 5,1-122,6). Kadar sTfR dapat dipergunakan sebagai indikator bangkitan kejang demam dengan cut-off point kadar sTfR adalah 2,55 μg/mL.Simpulan: Parameter sTfR merupakan faktor risiko bangkitan kejang demam.